2018
DOI: 10.1016/s2213-2600(17)30474-5
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapy breathing retraining for asthma: a randomised controlled trial

Abstract: SummaryBackgroundDespite effective pharmacotherapy, asthma continues to impair quality of life for most patients. Non-pharmacological approaches, including breathing retraining, are therefore of great interest to patients. However, clinicians rarely advocate breathing retraining and access to this intervention is restricted for most patients due to the limited availability of suitable physiotherapists and poor integration of breathing retraining into standard care. We aimed to assess the effectiveness of a dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
92
1
15

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(124 citation statements)
references
References 32 publications
3
92
1
15
Order By: Relevance
“…A randomized controlled trial in 94 adults with asthma demonstrated an equal response to breathing retaining in participants with a baseline NQ score of less than 23 (suggesting no DB symptoms) and more than or equal to 23 (suggesting DB symptoms). 34 In this service evaluation, DB symptoms (NQ scores) significantly improved in children with both a baseline score of less than 23 and more than or equal to 23; however, participants with a baseline score of more than or equal to 23 had a significantly greater response. These data suggest that although a baseline NQ score more than or equal to 23 strongly correlated with DB, it was not sensitive enough to identify children who would benefit from breathing retraining, therefore, the NQ questionnaire should not be used in isolation in clinical practice.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…A randomized controlled trial in 94 adults with asthma demonstrated an equal response to breathing retaining in participants with a baseline NQ score of less than 23 (suggesting no DB symptoms) and more than or equal to 23 (suggesting DB symptoms). 34 In this service evaluation, DB symptoms (NQ scores) significantly improved in children with both a baseline score of less than 23 and more than or equal to 23; however, participants with a baseline score of more than or equal to 23 had a significantly greater response. These data suggest that although a baseline NQ score more than or equal to 23 strongly correlated with DB, it was not sensitive enough to identify children who would benefit from breathing retraining, therefore, the NQ questionnaire should not be used in isolation in clinical practice.…”
Section: Discussionmentioning
confidence: 75%
“…A randomized controlled trial in 94 adults with asthma demonstrated an equal response to breathing retaining in participants with a baseline NQ score of less than 23 (suggesting no DB symptoms) and more than or equal to 23 (suggesting DB symptoms) . In this service evaluation, DB symptoms (NQ scores) significantly improved in children with both a baseline score of less than 23 and more than or equal to 23; however, participants with a baseline score of more than or equal to 23 had a significantly greater response.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were then guided thorough the breathing control exercise which involved breathing with an inspiratory time of two seconds, an expiratory time of two seconds and a post expiratory pause of one second (i.e. total respiratory cycle time = 5 seconds, with the aim of achieving a resting respiratory rate of 12 breaths per minute) (Thomas et al, 2003;Bruton et al, 2018;Bott et al, 2009). If when teaching breathing control, patients were unable to reduce excessive upper chest movements, they were instructed to place both hands behind their head to help fix the upper chest and reduce upper chest motion.…”
Section: Physiotherapy Interventionmentioning
confidence: 99%
“…Patients were instructed that the aim of the breathing exercise was to slowly and progressively increase tolerance of the imposed breathing pattern and rate. All patients were advised to undertake breathing control exercise for 15 minutes twice daily (Bruton et al, 2018;Cooper et al, 2003).…”
Section: Physiotherapy Interventionmentioning
confidence: 99%
“…A randomised controlled trial has assessed the effect on quality of life of digital self-guided breathing retraining exercises for people with asthma 1. The trial included 655 patients aged 16-70 years recruited from 34 UK general practices.…”
mentioning
confidence: 99%